Proceedings of the International Conference on Food, Agriculture and Natural Resources (FANRes 2018) 2018
DOI: 10.2991/fanres-18.2018.50
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Rice Farmers to Apply Warehouse Receipt System in Bantul Indonesia: Theory of Planned Behavior Approach

Abstract: The Warehouse Receipt System is one of the solutions of meager rice prices because it has the concept of delaying the sale of grain which aims to get a better selling price. Management performance and policy will affect farmers' interest in implementing the Warehouse Receipt System. This study aims to determine the interest of farmers in implementing the Warehouse Receipt System and to analyze the relationship between the characteristics of farmers and their interests. Sampling was conducted by way of purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The survey was conducted in July and August 2021. Subjective norms 5 [10][11][12] Perceived behavioral control 5 [10,14,44] Perceived ease of use 4 [1,45,46] Perceived usefulness 3 [44][45][46] Perceived cost 5 [1] Innovation openness 3 [47,48] Organizational factors 10 [1,48] An official application was made to the Scientific Research and Publication Ethics Committee of Cukurova University, Institute of Natural Sciences before commencing the field study. The questionnaire underwent a comprehensive assessment by this committee, and all requisite permissions were accordingly secured, as indicated in the official letter dated 8 July 2021 (protocol code E.135855).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The survey was conducted in July and August 2021. Subjective norms 5 [10][11][12] Perceived behavioral control 5 [10,14,44] Perceived ease of use 4 [1,45,46] Perceived usefulness 3 [44][45][46] Perceived cost 5 [1] Innovation openness 3 [47,48] Organizational factors 10 [1,48] An official application was made to the Scientific Research and Publication Ethics Committee of Cukurova University, Institute of Natural Sciences before commencing the field study. The questionnaire underwent a comprehensive assessment by this committee, and all requisite permissions were accordingly secured, as indicated in the official letter dated 8 July 2021 (protocol code E.135855).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, when attitude toward behavior exists, each belief leads behavior to a positive or negative result [16]. As Widodo and Sholichah [10] stated, attitudes toward behavior have positive effects on farmers' intention to prefer WRS. Some other studies also indicated that farmers who have a more positive attitude toward new systems in agriculture tend to adopt them more [22][23][24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations